2011
DOI: 10.3389/fendo.2011.00009
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Adverse Effects of Mono-Ethylhexyl Phthalate on Steroidogenesis in Immature Granulosa Cells and Rat Leydig cell Progenitors in vitro

Abstract: Di-(2-ethylhexyl) phthalate, one of the phthalates most widely distributed in the environment, causes reproductive toxicity that is attributable to the action of its primary metabolite, mono-(2-ethylhexyl) phthalate (MEHP). Here, we have investigated the effects of MEHP on steroidogenesis by primary cultures of rat Leydig cell progenitors and immature granulosa cells. This phthalate stimulated basal steroidogenesis and steroidogenic acute regulatory protein (StAR) expression in both types of steroidogenic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Further, MEHP exposure for 24 h at 100 μM decreased progesterone production and FSH-induced cAMP accumulation in rat granulosa cells ( 164 ). In contrast, MEHP exposure for 48 h at 100–250 μM in a different study increased basal steroidogenesis in rat granulosa cells, evident by increases in progesterone and protein levels of STAR ( 165 ). Perhaps the discrepancy in the MEHP-induced defects in steroidogenesis can be attributed to the dosage and use of different rat strains and the different susceptibilities to phthalate toxicity across strains.…”
Section: Effects Of Phthalates On Steroidogenesismentioning
confidence: 82%
“…Further, MEHP exposure for 24 h at 100 μM decreased progesterone production and FSH-induced cAMP accumulation in rat granulosa cells ( 164 ). In contrast, MEHP exposure for 48 h at 100–250 μM in a different study increased basal steroidogenesis in rat granulosa cells, evident by increases in progesterone and protein levels of STAR ( 165 ). Perhaps the discrepancy in the MEHP-induced defects in steroidogenesis can be attributed to the dosage and use of different rat strains and the different susceptibilities to phthalate toxicity across strains.…”
Section: Effects Of Phthalates On Steroidogenesismentioning
confidence: 82%
“…It was found to decrease viability as well as steroidogenic potential of mouse Leydig tumor cells (Piché et al, ). This phthalate stimulated basal steroidogenesis and steroidogenic acute regulatory protein (StAR) expression in both types of steroidogenic cells (Svechnikova, Svechnikova, & Söder, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to acrosome biogenesis defects, we observed a decrease in sperm count; this appears to be a common phenotype for a variety of genetic defects that perturb the normal programme of mouse spermiogenesis (Kang-Decker et al, 2001;Venables and Cooke, 2000;Wang et al, 2014). Bell et al (2014) found that the histone to protamine transition was disrupted in Sirt1-deficient spermatids, and this might partially account for the decrease in sperm count.…”
Section: Discussionmentioning
confidence: 68%
“…Leydig cells were isolated as previously described, with minor modifications (Svechnikova et al, 2011). Briefly, the 2-month-old mice were euthanized by cervical dislocation, and the testes were removed and washed three times with PBS.…”
Section: Isolation and Primary Culture Of Leydig Cellsmentioning
confidence: 99%